Contributing Factors of Production Performance in the Food Processing Industry - Nurdiyana Nazihah Zainal; Siti Fairuza Hassam; Mohd Rizaimy Shaharudin; Jamaludin Akbar; Muhammad Amin Mustafa (International Journal of Supply Chain Management, 2018)
The main purpose of this study is to determine the factors that can contribute to the production performance in the food industry. This study can help to identify the contributing factors towards the production performance. Five factors were identified based on the past literature. 100 food processing manufacturers with the majority coming from small and medium industries (SME) have been selected. The purposive sampling technique has been selected for this study with the total number of usable questionnaires received being from 80 respondents. The collected data was analysed using SmartPLS 3.0 to test the relationships between the independent variables and the dependent variable of the study. The results showed that the Total Quality Management (TQM), Lean Management (LM), and Hazard Analysis and Critical Control Point (HACCP)significantly influenced the production performance. The practical implications of these outcomes are further discussed in the study.